Efektivitas Kebijakan Penggunaan Kantong Belanja Ramah Lingkungan terhadap Pengurangan Timbulan Sampah Plastik di Provinsi Jakarta : Kajian Literatur - Indriani, Farida Maya; Lestari, Maharyati Puji; Maryono, Maryono (Universitas Hang Tuah Pekanbaru, 2025)
Ignoring plastic waste management systems can threaten the sustainability of the environment and living creatures in the universe. The alarming amount of plastic waste shows the failure of waste management systems and demands serious control through the use of environmentally friendly materials that can reduce ecological impacts and encourage sustainable changes in consumer behavior. In an effort to control and reduce the generation of single-use plastic waste in Jakarta, Provincial Government issued “DKI Jakarta Provincial Governor Regulation Number 142 of 2019 concerning the Obligation to Use Environmentally Friendly Shopping Bags in Shopping Centers, Supermarkets and People's Markets”. This paper aims to analyze the effectiveness of single-use plastic waste control after the enactment of the regulation and compare similar policies in several countries. The method used is through literature review by reviewing various literature sourced from scientific journals and relevant research reports. The results of the study state that the implementation of the policy on the use of eco-friendly shopping bags has been able to reduce the amount of plastic waste generation and increase the use of Environmentally Friendly Shopping Bags in Jakarta Province and several countries that implement similar policies. The government must create an ecosystem that supports policy implementation through massive and sustained public campaigns and education to build understanding and change public behavior so that people are more prudent in reducing their use of single-use plastic bags.